2022
DOI: 10.3390/plants11152068
|View full text |Cite
|
Sign up to set email alerts
|

Functional Ecology of External Secretory Structures in Rivea ornata (Roxb.) Choisy (Convolvulaceae)

Abstract: Plants have evolved numerous secretory structures that fulfill diverse roles and shape their interactions with other organisms. Rivea ornata (Roxb.) Choisy (Convolvulaceae) is one species that possesses various external secretory organs hypothesized to be ecologically important. This study, therefore, aimed to investigate five secretory structures (nectary disc, petiolar nectaries, calycinal glands, staminal hairs, and foliar glands) using micromorphology, anatomy, histochemistry, and field observations of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 113 publications
0
3
0
Order By: Relevance
“…The histochemical and fluorescence assays showed the presence of lipid compounds (total lipids, acidic, and neutral lipids) and phenolic compounds (total phenols, phenolic acids, and flavonoids) in the tissues and glandular trichomes of the D. moldavica nectary. Various authors also reported the presence of similar groups of metabolites in nectaries of other plant species [ 57 , 58 , 59 , 60 ]. Similar to the present findings, these researchers showed that the metabolites were located in the nectary epidermis and/or parenchyma; next, the compounds penetrated into the secreted nectar.…”
Section: Discussionmentioning
confidence: 87%
“…The histochemical and fluorescence assays showed the presence of lipid compounds (total lipids, acidic, and neutral lipids) and phenolic compounds (total phenols, phenolic acids, and flavonoids) in the tissues and glandular trichomes of the D. moldavica nectary. Various authors also reported the presence of similar groups of metabolites in nectaries of other plant species [ 57 , 58 , 59 , 60 ]. Similar to the present findings, these researchers showed that the metabolites were located in the nectary epidermis and/or parenchyma; next, the compounds penetrated into the secreted nectar.…”
Section: Discussionmentioning
confidence: 87%
“…Our pollinator observations indicate that both A. versicolor and A. mekongensis are pollinated by carpenter bees. Previous studies have generally reported that Convolvulaceae species are mainly pollinated by bees ( Galetto and Bernadello 2004 ; Maimoni-Rodella and Yanagizawa 2007 ; Pick and Schlindwein 2011 ; Hassa et al 2023 ) or by bees and butterflies ( Hassa et al 2020 ; Jirabanjongjit et al 2021 ) or by hawkmoths ( Willmott and Burquez 1996 ; McMullen 2009 ; Chitchak et al 2022 ). Pollination studies of Argyreia are scarce compared to sister genera such Ipomoea , but Chitchak et al (2018) did report that Xylocopa nasalis visits Argyreia gyrobracteata and receives pollen on its head.…”
Section: Discussionmentioning
confidence: 99%
“…Extrafloral nectaries are also considered as storage organs for secondary metabolites. Cassava, tapioca, passiflora, cotton, cashew nut trees, and several members of the Rosaceae have been reported to emit secondary metabolites from extra floral nectaries that aid in luring predators of various pest species [ 108 , 109 ].…”
Section: Storage Of Secondary Metabolitesmentioning
confidence: 99%